Kontroversi ’Aul dalam Hukum Waris Islam dan Praktiknya di Indonesia - Kasman Bakry; Muhammad Nirwan Idris; Fadlan Akbar; Kurnaemi Anita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to uncover the controversy of 'aul in the concept of Islamic inheritance' and the method of the majority of scholars in tarjÄ«h this problem and how it is practiced in Indonesia. This research is a qualitativeresearch with a normative juridical approach that focuses on literature review and comparative analysis. The results of the study found that 'Umar bin al-Khaá¹á¹Äb viewed that the concept of 'aul was a solution to the problem of inheritance which experienced an increase or excess in the origin of the problem which was not sufficiently divided among all heirs. As for 'Abdullah bin 'AbbÄs mentioned that if the inheritance is not enough to be distributed to all the heirs, then the one who has the strongest position among the heirs will take precedence over the inheritance rights. The majority of scholars then determined the solution to the inheritance problem that experienced 'aul by interpreting the words of 'Umar bin al-Khaá¹á¹Äb, namely using the concept of 'aul. Then it was found that the application of the problem of 'aul in inheritance in Indonesia is considered still not optimal and even barely implemented. This is triggered by several factors including not too interested in the community and not yet aware of the importance of applying sharia law in inheritance issues. This research is expected to contribute thinking and education as a complement and valuable solution for inheritance problems in the Muslim community.